Pengetahuan Guru PJOK Sekolah Dasar pada Implementasi Kurikulum Merdeka di Kecamatan Baturraden, Banyumas - Ikhsan, Fadilah; Febrianta, Yudha (Indonesian Journal Publisher, 2023)
This study aims to find out the knowledge of physical education teachers in primary schools regarding implementing the Merdeka curriculum in the Baturraden district. This research used a survey method with data collection technique using a questionnaire provided directly. The subjects in this study were all physical education teachers in primary schools in Baturraden district, amounting to 20 teachers from 26 schools. The data analysis technique used descriptive quantitative analysis, presented as percentages. The results of this study showed that the knowledge of physical education teachers in primary schools about implementing the Merdeka curriculum in the Baturraden district had an average score of 31.5 in the 24.5 X 31.5 interval or is in a good category. In detail, it can be shown that 30% or 6 teachers have excellent knowledge, 65% or 13 teachers have good knowledge, 5% or one teacher have relatively good knowledge, 0% have less good knowledge, and 0% have poor knowledge. Several obstacles encountered by physical education teachers include not fully understanding the guidebook in the Merdeka curriculum and self-adjustment to the Merdeka curriculum. This study is expected to reflect that physical education teachers improve their knowledge of implementing the Merdeka curriculum.